Accuracy evaluation of ACI and EC2 on minimum reinforcement ratio for RC beams - Chandra, Gilbert Nathanael (Nanyang Technological University, 2021)
Sectional analysis by using software Response2000 has been carried out to calculate minimum flexural reinforcement ratio by considering the size effect and the cross-section shape of the beam which are completely neglected by ACI 318-19 and EC2, as well as extending the current upper limit on the yield strength of reinforcement (fy) on ACI 318-19 and EC2 to enable the usage of high strength steel reinforcement (HSSR). A total of 1920 test results were used to analyze the parameters affecting the minimum flexural reinforcement ratio to ensure a ductile failure mode. The research has revealed that the minimum flexural reinforcement ratio is a function of 4 variables: concrete compressive strength (f’c), reinforcement yield strength (fy), d/h ratio, and cross-section shape. Furthermore, this report has shown that ACI 318-19 is more conservative than EC2 for predicting the minimum reinforcement ratio. Finally, new equations have been proposed to calculate the minimum flexural reinforcement ratio.